Challenges in the Protection of Domestic Violence Victims in Azerbaijan: An Overview of the National Legislation in Light of the 2011 CoE Istanbul Convention - Alasgarova, Gulnaz (Teisė, 2019)
This article focuses on the following issues: the list of people offered victim status under the Law on Prevention of Domestic Violence of Azerbaijan, the legal remedies available to them, and the legal measures taken by state authorities in all kinds of domestic violence episodes. Additionally, the Law is scrutinized in light of the CoE Convention on Preventing and Combating Violence against Women and Domestic Violence. Hence, the benefits and shortcomings of the current legislation are easily found.
Keywords: domestic violence; victims; protection orders; resumption of family affairs; states` obligations